Analysis of Parang Mask Batik Character Education as a Form of Character Building for Elementary School Children - Regina, Belinda Dewi; Wijayaningputri, Arinta Rezty (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2020)
Batik is one of the crafts in Indonesia. The form and function of batik has developed. Formerly used by the royal court, now it is not. Every batik work produced has a character in it. These characters are found in their cultural background, beliefs, customs, and tastes. This makes batik a vehicle for cultivating character values. It is feared that the potential for Indonesian batik will be eroded without the preservation of Indonesian society. Although Indonesia has produced a lot of batik, there are still a few that show its distinctive features. Recently, batik appears in Malang, but it does not have a patent right. So it does not yet have a unique batik motif. Even though it does not have a patent right, there is batik that is well known in Malang, namely the Parang Mask batik from the Panji figure. In the batik motif is associated with the values of character education including religious, nationalist, independent, mutual cooperation and integrity as a form of character building for elementary school children. Therefore, the purpose of this study is to describe the character education of Parang Mask batik as a form of character building for elementary school children. This study uses a qualitative approach with this type of descriptive research. The subject is Parang Mask batik. The character values in the Parang Mask batik are religious values, nationalist values and also the value of mutual cooperation.